Pengaruh Supervisi Akademik dan Gaya Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru SMA Negeri Program Sekolah Penggerak Sekecamatan Kayuagung - Ida Farida; Nur Ahyani; Syaiful Eddy (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine the influence of the principal's supervision and leadership style on the performance of public high school teachers in the driving school program. The research method is descriptive analysis with a quantitative approach. The research population is all school principals and teachers, totaling 137 people, and a sample of 58 people was selected based on the proportional random sampling technique. Based on the data processing results with the help of the SPSS version 25 for the Windows program, the regression coefficient value for the academic supervision variable (X1) was found to be 0.603 with a positive value. Tcount was 5.554 > ttable 2.004 with a significance level of 0.000 < 0.05. For the leadership style variable ( X2), The value of the regression coefficient obtained is 0.629 positive value, and tcount of 5,805> ttable 2,004 with a significant level of 0.000 <0.05. Then, the results (F test) show an Fcount value of 20,476 > Ftable 3.16 for a significance level of 0.000 < 0.05. In conclusion, leadership influences teacher performance, and educational supervision influences teacher performance, then school culture influences teacher performance, and the principal's leadership, academic supervision, and school culture influence teacher performance. Keywords: Academic Supervision, Leadership Style, Teacher Performance,